2016
DOI: 10.7567/jjap.55.06jb03
|View full text |Cite
|
Sign up to set email alerts
|

Application of patterned Ag-nanowire networks to transparent thin-film heaters and electrodes for organic light-emitting diodes

Abstract: We present patterned Ag-nanowire (AgNW) networks for their application to transparent electrodes in flexible devices. Using capillary-force-based soft lithography (CFL), we formed 25- to 30-µm-wide line patterns of AgNWs on flexible polymer substrates. Organic light-emitting diodes (OLEDs) and transparent thin-film heaters (TFHs) were successfully fabricated on the patterned substrates, which verified the potential of AgNW patterns formed by CFL as interconnects in flexible devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Gravure printing, lift-off lithography, and laser patterning are the commonly used methods for the precise patterning of AgNWs. Even though these techniques are effective in patterning AgNWs, they face several drawbacks, such as multiple-step processes, limited patterning shapes, postprocess chemical residues, and expensive equipment . However, capillary force lithography (CFL) has been shown to be an excellent alternative patterning technique …”
Section: Introductionmentioning
confidence: 99%
“…Gravure printing, lift-off lithography, and laser patterning are the commonly used methods for the precise patterning of AgNWs. Even though these techniques are effective in patterning AgNWs, they face several drawbacks, such as multiple-step processes, limited patterning shapes, postprocess chemical residues, and expensive equipment . However, capillary force lithography (CFL) has been shown to be an excellent alternative patterning technique …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aligned network of TCEs is favorable to device performances and can reduce the fine pattern failure rate. MNW patterns can also be obtained via a CFL process. , As shown in Figure c, the PDMS stamp with grooves of interdigitated rectangular line patterns was first placed in contact with the precoated AgNW film. Then, a UV-curable hydrogel solution was dropped at the edge of the PDMS stamp, and it can flow into and fill the cavities of the PDMS by a capillary force.…”
Section: Subtractive Patterning Methodsmentioning
confidence: 99%
“…For AgNW electrodes to be used as electrodes for deformable displays such as OLED and micro-LED display, high-resolution patterning must be possible because high image resolution should be obtained under mechanical deformation. A large number of studies have been reported for the fine patterning of AgNW electrodes, which includes photolithography using photoresists, poly­(dimethylsiloxane) (PDMS) stamps, lasers, and insulator printing methods. Photolithography is a widespread method for the fine and precise patterning of AgNW electrodes. Much effort has been made to reduce its use in the actual process because photolithography is expensive and cumbersome at the same time. Laser patterning is efficient because it can make patterns directly in one step without any use of photomasks or chemical etching processes, but it has the disadvantage of requiring expensive equipment and slow production speed.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method needs optimization of the AgNW ink considering AgNW content, surface energy modifiers, and organic binders. Unlike these methods, simple AgNW patterning processes that use capillary flow characteristics of the AgNW solution using PDMS stamps have been published, , but they have a limitation in forming uniform patterns in a large area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation